Plant growth‐promoting activity of endophytic bacteria from sweet sorghum (Sorghum bicolor (L.) Moench) - Charlie Ester de Fretes; Donny Widianto; Yekti Asih Purwestri; Tri Rini Nuringtyas (Indonesian Journal of Biotechnology, 2021)
Application of high levels of chemical fertilizers for optimal growth of sweet sorghum causes environmental degradation. Plant growth‐promoting bacteria have biotechnological importance because they can improve the growth and health of important agronomic plants. This study aimed to isolate, characterize, and identify endophytic bacteria associated with sweet sorghum (cv. KCS105), and also to study the inoculation effects of selected isolates on sorghum growth. In this study, 35 isolates were evaluated for their ability to support plant growth. The results showed that seven isolates were diazotrophic, six were capable of dissolving phosphate, six produced IAA and could detect ACC‐deaminase activity, and three inhibited the growth of pathogenic fungi. Nine isolates exhibiting mechanisms for promoting plant growth from the Alphaproteobacteria (Devosia), Firmicutes (Bacillus, Paenibacillus, Staphylococcus), and Actinobacteria (Microbacterium, Brachybacterium) phyla were identified. In addition, the Paenibacillus sp. BB7, Bacillus sp. PIB1B, and Bacillus sp. PLB1B isolates showed increasing effects on plant growth in greenhouse tests. Endophytic bacterial isolates which display plant growth‐promoting features can potentially be employed as biofertilizer agents. They may also address environmental damage problems resulting from the use of chemical fertilizers and pesticides.